Fifteen years of cold matter on the atom chip: promise, realizations, and prospects. Issue 18 (10th October 2016) - Keil, Mark; Amit, Omer; Zhou, Shuyu; Groswasser, David; Japha, Yonathan; Folman, Ron
Abstract : Here we review the field of atom chips in the context of Bose–Einstein Condensates (BEC) as well as cold matter in general. Twenty years after the first realization of the BEC and 15 years after the realization of the atom chip, the latter has been found to enable extraordinary feats: from producing BECs at a rate of several per second, through the realization of matter-wave interferometry, and all the way to novel probing of surfaces and new forces. In addition, technological applications are also being intensively pursued. This review will describe these developments and more, including new ideas which have not yet been realized.